2007
DOI: 10.1002/pi.2295
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and thermal dissociation of 2‐butoxyethanol‐blocked diisocyanates and their use in the synthesis of isocyanate‐terminated prepolymers

Abstract: A series of blocked diisocyanates has been synthesized from toluene diisocyante (TDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), 4,4′‐diphenylmethane diisocyanate (MDI) and 2‐butoxyethanol. The synthesis of blocked diisocyanate adducts was confirmed by Fourier transform infrared, 1H NMR, electron impact mass spectrometry and nitrogen analysis. Differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA) and carbon dioxide evolution were used to determine the minimum de‐bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
(25 reference statements)
0
23
1
Order By: Relevance
“…In addition, we observed that the deblocking temperature obtained by TGA was different from that measured by DSC. This was due to differences in sample pans and thermal effects in these two instruments (1,10). Based on our study, the deblocking temperature measured by TGA was greater than that obtained by DSC measurement.…”
Section: Deblocking Temperaturecontrasting
confidence: 59%
See 2 more Smart Citations
“…In addition, we observed that the deblocking temperature obtained by TGA was different from that measured by DSC. This was due to differences in sample pans and thermal effects in these two instruments (1,10). Based on our study, the deblocking temperature measured by TGA was greater than that obtained by DSC measurement.…”
Section: Deblocking Temperaturecontrasting
confidence: 59%
“…The onset of deblocking reaction has been determined by many analytical techniques (1,10,30). It should be noted that the reported deblocking temperatures frequently depend on the characterization technique, heating rate, and other variables.…”
Section: Deblocking Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The band at 1745 cm À1 was C=O stretching of the urethane group, and the strong band at 1223-1267 cm À1 corresponded to the stretching vibrations of C=O combined with NH in all the spectra. 28 The band at 1607-1606 cm À1 was benzene ring, the bands at 1533-1539 cm À1 correspond to carbamate, and the band at 2940-2926 and 2861-2853 cm À1 was asymmetric and symmetric C-H stretching of CH 2 , respectively. The absorption peaks of NCO at 2277 cm À1 and epoxide groups at 917 cm À1 also appeared in Fig.…”
Section: Ir Spectramentioning
confidence: 99%
“…Commercial blocking agents include phenol, caprolactam, methyl ethyl ketoxime, amines, dimethyl pyrazoles, diethyl malonates, sodium bisulte and many others. [17][18][19][20] The rate and extent of deblocking reaction depend on many factors: the structure of isocyanate and blocking agent including substituents, solvents, catalysts, temperature and the thermal stability of the isocyanate-blocking agent bond.…”
Section: -16mentioning
confidence: 99%